KONSEP PENDIDIKAN ISLAM BAGI PEREMPUAN PERSPEKTIF NYAI KHAIRIYAH HASYIM DAN RELEVANSINYA DALAM PENDIDIKAN PEREMPUAN DI MASA MODERN - Al Azizah, Soraya; Irwan, Irwan; Rahmah, Sri; Febrica, Sonia; Shobariyah, Siti; Suarsih, Suarsih (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
Nyai Khairiyah Hasyim is a female ulama or Islamic scholar from Jombang, who has a great concern on the development of women. Her concern is shown through her involvement in the management of the Seblak Female Islamic Boarding School and the establishment of the Kuttabul Banat Madrasah, which is specifically built for Saudi Arabian women. Through this educational institution, Nyai Khairiyah Hasyim seeks to give rights to women to have the same opportunities as men in terms of being educated and having the opportunity to develop all of their potential. The objective is making it possible for women to live independently. The efforts Nyai Khairiyah Hasyim have made at the same time refute the negative assumptions of the society. Those assumptions include the statements saying that women are weak people who can only depend on men, women do not deserve the opportunity to get an education because their final task is merely being at home to take care of the household, and women are always discriminated in all fields. The objectives of this study are: (1) To find out the concept of Islamic education for women based on NyaiKhairiyah Hasyim’sperspective; (2) To find out the relevance of the Islamic education concept for women based on Nyai Khairiyah Hasyim’s perspective on women's education in modern times. This study employs a qualitative approach usinga historical research as the type of study to examine the contribution of the Islamic scholar. The data collection techniques are carried out through interviews and literature studies, through primary reference sources and other sources supportingthe study. The results of the study indicate that, (1) The Islamic education for women aims to develop intellectual abilities, skills and personality according to Islamic teachings. Nyai Khairiyah Hasyim implements a gender equality-based curriculum. There are several classical education methods applied by Nyai Khairiyah Hasyim, such as the sorogan, bandongan, deliberation and exemplary methods. The relationship between educators and students in Nyai Khairiyah Hasyim's perspective should be the one like what parents and children have. (2) The concept of Islamic education for women, based on Nyai Khairiyah Hasyim's perspective, is relevant to women's education in modern times because it can be an answer to the challenges of the modern development while still prioritizing the dignity of women..